2003
DOI: 10.1002/pi.1148
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of poly(4‐vinylpyridine) N‐alkyl quaternized at the chloroform/water interface

Abstract: The Du Noüy method has been employed to study the interfacial properties of poly(4‐vinylpyridine) N‐n‐alkyl quaternized with hexyl, octyl and decyl bromide, at the chloroform/water interface. The interfacial tension is highly dependent on the hydrophilic–hydrophobic balance between the pyridinium group and the length of the polyelectrolyte side aliphatic chain. The excess interfacial concentration, Γ, is determined according to the Gibbs–Szyszkowski equation. The areas covered by monomer unit at the interface,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…In order to quantify the adsorption process, the following form of the Gibbs equation was used [26]:…”
Section: Resultsmentioning
confidence: 99%
“…In order to quantify the adsorption process, the following form of the Gibbs equation was used [26]:…”
Section: Resultsmentioning
confidence: 99%
“…Cationic polyelectrolytes can be easily obtained by N-alkylation of poly(4-vinylpyridine) using alkyl halides of various alkyl chain lengths [1][2][3] to control the amphiphilic character of quaternized polyvinylpyridine (QPVP). For QPVP carrying very short alkyl groups (H, methyl or ethyl) electrostatically driven adsorption onto negatively charged solid surfaces has been studied over the last 20 years [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…For QPVP carrying very short alkyl groups (H, methyl or ethyl) electrostatically driven adsorption onto negatively charged solid surfaces has been studied over the last 20 years [1][2][3][4][5][6][7][8][9][10][11][12]. Kawaguchi and co-workers [4] showed that the adsorption of QPVP onto nonporous silica increased with increasing KBr concentration due to a decrease in the excluded volume of polymer chains.…”
Section: Introductionmentioning
confidence: 99%
“…pyridinium bromide), QPVP-C5 Bromide salt of PVP quaternized with linear pentyl chains was prepared in a flask with a reflux condenser by dissolving PVP (10 wt%) in anhydrous ethanol, adding the 1-bromopentane with an excess of 5 times the stoichiometric amount and keeping the mixture stirring under nitrogen atmosphere for 24 h at 60°C [23,24], as schematically represented in Figure 2. The mixture was then precipitated in diethyl-ether to obtain a slightly yellow solid that was re-dissolved in ethanol and re-precipitated the same way.…”
Section: Preparation Of Poly(4-vinyl-n-pentylmentioning
confidence: 99%